Rifling Through My Drawers - Dickson Wright, Clarissa (United Kingdom Hodder & Stoughton, 2009)
Bestselling author of SPILLING THE BEANS and champion of the countryside brings us her outspoken views, encounters and stories from her life as she travels around the heart of Britain.
Include Illustration
Keywords: Manners and Customs -- Dickson Wright, Clarissa -- Celebrity Chefs